Infeluence des paramètres géomécaniques sur la stabilité des pentes rocheuses ( Cas des Gorges de Kherrata ) - RAHMOUNI ,Nadjim; ZAHRI, Farid (Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2017)
This paper is devoted to the study of problems of stability of rock slopes under the influence of the different geomechanical parameters of the discontinuities which could be the most important factor controlling the stability of the rock mass. The kinematic analysis allows to reveal the different modes of rupture. The results of the SMR classification show that the breaks are almost all unstable, constituting hazards that are potentially characterized by the fall of blocks that are more numerous in the study area and that threaten road users when the vulnerability of this network is high. The crossing between hazard and vulnerability determines the risk of falling blocks in slopes. The main objective of this work is based on the prioritization and qualification of the risk of falling blocks using a quantitative scoring method (RHRS: Rockfall Hazard Rating System) which allows the risk to be ranked on each homogeneous section studied after the evaluation Of all the scores of the criterion governing the fall hazard and the criteria that control the vulnerability of the road network. The application of this method makes it possible to prioritize 743 meters of length qualified from high to very high risk over a total length of 1100 meters. In order to assess these risks, the definition of the Isevere solutions required by the protection and reinforcement structures proposed for the construction in the rocky slopes most exposed to reduce the risk.
هذه المذكرة مخصصة لدراسة مشاكل استقرار المنحدرات تحت تأثير مختلف الخصائص الجيوميكانيكية التي قد تكون من ابرز عوامل السيطرة على استقرار الكتل الصخرية. التحليل الحركي يسمح باستخراج مختلف طرق . الانكساراتدل على أن معضم الانكسارات تقريبا غير مستقر يحتمل أن تشكل تطور ا لظاهرة تساقط SMR نتائج التصنيف الاحجار والتي تم تسجيلها بكثرة في منطقة الدراسة وهذا ما يهدد مستخدمي الطريق وخاصةعندما تكون حساسية الطريق عالية. الاتحاد بين نشاة الضاهرة وحساسية الطريق يحدد خطر سقوط الكتل الصخرية من المنحدر. الغرض الرئيسي من هذا العمل يرتكز على تقسيم وتصنيف مخاطر القطع المتساقطة بطريقة حسابية كمية تسمى نظام تقييم مخاطر الانهيار الصخري ( التي تسمح بتقسيم خطر كل قطعة متجانسة مدروسة RHRS) بالنقاط بعد تقييم جميع الدرجات من المعاييرا التي تحكم. في خطر السقوط والمعايير التي تتحكم في ضعف شبكة الطريق تطبيق هذه الطريقة سمحت بتقسيم 743 متر من الطول مصنفمن قوي إلى خطر قوي جدا من الطول الإجمالي المقدر ب 1100 متر. في نهاية تقسيمهذه المخاطر، تعريف مجموعة من الحلول يكون لازم بعض مشاريع الحماية و التدعيم مقدمة للانجاز في المنحدرات الصخرية الاكثر عرضة للخطر وهاذ للتقليل و للحد من هذه المخاطر.
Keywords: Stabilité; Massif rocheux; Rupture; Risque; Discontinuités